Intersections of ultracold atomic polarons and nuclear clusters: how is a chart of nuclides modified in dilute neutron matter? - Hiroyuki Tajima; Hajime Moriya; Wataru Horiuchi; Eiji Nakano; Kei Iida (AAPPS Bulletin)
Abstract Neutron star observations, as well as experiments on neutron-rich nuclei, used to motivate one to look at degenerate nuclear matter from its extreme, namely, pure neutron matter. As an important next step, impurities and clusters in dilute neutron matter have attracted special attention. In this paper, we review in-medium properties of these objects on the basis of the physics of polarons, which have been recently realized in ultracold atomic experiments. We discuss how such atomic and nuclear systems are related to each other in terms of polarons. In addition to the interdisciplinary understanding of in-medium nuclear clusters, it is shown that the quasiparticle energy of a single proton in neutron matter is associated with the symmetry energy, implying a novel route toward the nuclear equation of state from the neutron-rich side.